PROTECTIVE EFFICACY OF Tribulus terrestris ON ATRAZINE EXPOSED FRESH WATER FISH Oreochromis mossambicus (W.K.H Peters, 1952) - NIMAVATHI, V.; JAYANTHI, J.; RAGUNATHAN, M. G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Atrazine is considered moderately toxic to aquatic animals. In the present study protective effect of Tribulus terrestris on hepatotoxicity in fresh water fish Oreochromis mossambicus, at sub lethal concentration of atrazine (16.5 mg/l) exposure fish for 120 h was studied. After completing the exposure time experiment were carried out to find the level of lipid peroxidation, reduced glutathione, superoxide dismutase, catalase and glutathione peroxides (LPO, GSH, GPx, SOD, and CAT) activities in liver tissues. The results showed increases LPO and decreased level of GSH, GPx, SOD, and CAT when compared to normal. During the recovery period Tribulus terrestris (1.2g/l) plant exposure drastically restored to the normal level when compared to atrazine treatment. Present investigation concluded that the Tribulus terrestris significantly alters the metabolic activity in liver tissues of atrazine exposed fishes.